THE IMPACT OF EMPLOYEE ATTITUDE ON ORGANIZATIONAL COMMITMENT - Dedi Hadian; Senen Machmud; Soelaiman Sukmalana (STMIK Mardira Indonesia, Bandung, 2021)
The objective of this study was to determine the effect of the attitude component on employee commitment. The researcher's approach uses a survey approach conducted on employees of microfinance institutions in the city of Bandung. Respondents who were willing to fill out the research questionnaire were 78 employees. Researchers used path analysis to determine the magnitude of the influence of the attitude component on employee work commitment to answer the problem formulation. The results of the study indicate that the attitude component has a significant effect on work commitment. Therefore, the study results recommend the relevant parties to improve employee work attitudes so that work commitment can achieve optimally. Keywords : Attitude, Organizational commitment, Employee.